The Value of Switching Production Options in a Flexible Biorefinery. (21st March 2017) - Hossiso, Kassu Wamisho; Ripplinger, David
Abstract : This study analyses the value of a switching option in a flexible biorefinery plant that produces ethanol and sugar juice in a single plant using energy beets. A real-options approach is used to compute threshold prices and optimal switching decision rules for switching between sugar and ethanol production modes. The analysis shows that it is economically optimal to keep producing ethanol then switching to sugar juice, given the stochastic price parameters of the two products.